Modeling and Direct Torque Control (DTC) of the Doubly Fed Asynchronous Machine - BEGUI Mohammed Laid; NEGHMOUCHE NACER Aymen; SAYAH Abdelmadjid; SOUALAH MOHAMMED Abdallah (University of Shahid Hama Lakhdar - El Oued, 2024)
In this trail, a study of a DTC control of a doubly fed induction machine (DFIM), through a three, phase two-level converter connected to a stator has been presented. For this purpose, a state of, the art of the studied machine has been carried out. A mathematical model of the machine is presented using MATLAB. The DFIM which is fed by a three phase two-level PWM converter, has been modeled and its control approach has been given. Also, the problem of decoupling, between the flux and the torque has been treated. The simulation results display that the assigned objective has been reached. تتناول هذه المذكرة دراسة محرك لا تزامني ثلاثي الطور ثنائي التغذية، ذو عضو دوار ملفوف، بواسطة التحكم المباشر للعزم حيث تتم تغذية العضو الساكن بواسطة مموج ذو مستويين من أجل هذا تما عرض المحرك على الباحثين في هذا المجال، ثم انتقلنا بعد ذلك إلى إعطاء النموذج الرياضي للمحرك. ثم اتبعناه. بعد ذلك بمحاكاة، وبما أن تغذية المحرك تتم عبر مموج ذو مستويين، فقد قمنا بإعطاء النموذج الرياضي وطرق التحكم فيها أما فيما يتعلق بالفصل بين التدفق والعزم، فقد استعملنا التحكم المباشر للعزم الذي يوجها فيها العزم وفق العضو الدوار. حيث بينت نتائج المحاكاة أن الفصل بين التدفق والعزم قد تم فعلا
Master's thesis in electromechanics
Keywords: Keywords: DFIM; DTC; PWM converter; three phase-two level converter; Matlab.; محرك لا تزامني، التحكم المباشر للعزم، مموج، المتلاب.